Resonant optical rectification in bacteriorhodopsin - Groma, Géza I. (Proc Natl Acad Sci U S A, 2004)
The relative role of retinal isomerization and microscopic polarization in the phototransduction process of bacteriorhodopsin is still an open question. It is known that both processes occur on an ultrafast time scale. The retinal trans→cis photoisomerization takes place on the time scale of a few hundred femtoseconds. On the other hand, it has been proposed that the primary light-induced event is a sudden polarization of the retinal environment, although there is no direct experimental evidence for femtosecond charge displacements, because photovoltaic techniques cannot be used to detect charge movements faster than picoseconds. Making use of the known high second-order susceptibility χ((2)) of retinal in proteins, we have used a nonlinear technique, interferometric detection of coherent infrared emission, to study macroscopically oriented bacteriorhodopsin-containing purple membranes. We report and characterize impulsive macroscopic polarization of these films by optical rectification of an 11-fs visible light pulse in resonance with the optical transition. This finding provides direct evidence for charge separation as a precursor event for subsequent functional processes. A simple two-level model incorporating the resonant second-order optical properties of retinal, which are known to be a requirement for functioning of bacteriorhodopsin, is used to describe the observations. In addition to the electronic response, long-lived infrared emission at specific frequencies was observed, reflecting charge movements associated with vibrational motions. The simultaneous and phase-sensitive observation of both the electronic and vibrational signals opens the way to study the transduction of the initial polarization into structural dynamics.